Poetry and phenomenology. Methodical and content approaches: the poetic exercise and the Phenomenology (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
This article aims to present an analysis to an observed phenomenon during the last century, in which the language has been used in the field of Philosophy to talk about a linguistic twist that has wielded the poetic language as an expression of the Phenomenological way of thinking. Philosophers like Heidegger have incorporated this phenomenon; poeticize, into their works to return to generate a truth status through art, language, and poetry. Heidegger presents poeticize as a constitutive attitude of the man that puts the art in work to the Truth, called authentic existence. Finally, it is been analyzed pieces of notes about the phenomenological concepts of epojé and alétheia, and the possibility of their application to the poet’s attitude, the Heideggerian conception of poetry and his tendency to generate trough poeticize a new way of thinking.